Using reading journals to identify moral values in the extensive reading books - Prancisca, Stella; Rizqi, Muhammad Ainur (Universitas Islam Negeri Banda Aceh, 2024)
With the mushrooming popularity of extensive reading in language classrooms, teachers might be unaware that students are not only gaining linguistic inputs from their reading but also those related to non-linguistic ones, such as moral values. Frankly speaking, some values may suit their culture, but others may not. This research then aimed to investigate these non-linguistic inputs the students obtained when participating in the Extensive Reading ER program. This is important amid the domination of Western culture in stories that students mostly use. This research tried to identify the types of moral values students attained after attending a one-semester ER program. Also, it questioned if these values fit with the culture and place where they lived. Using the diary method, this research collected students’ post-reading journals over one academic semester. The journals should be filled in every time the students finish reading. Involving 30 students as participants, the research generated 397 entries, 13 on average. The data were analyzed by classifying the students’ responses into five principles of moral values proposed by the Indonesian Ministry of Education and Culture. This research found that most moral values in the ER program aligned with those in Indonesia, despite a few differences. It also provided two most frequent moral values that were surprisingly close to Western culture. This research shared some interesting discussion, including the possible reasons why these two categories have a strong domination, outperforming other categories. Finally, the research also provides important notes regarding what teachers should do and key suggestions for future research.